A review of the effect of resistance training with high and moderate intensities on the blood levels of cortisol and testosterone hormones in the muscle strength of people - Zobairullah Ahmadi; Habaib Perooz; Rahmullah Rahimi (Science and Education, 2024)
With increasing age, the body composition has changes that can include negative effects. Resistance training is one of the ways to reduce muscle mass and increase muscle diameter, which is considered to reduce muscle wasting (sarcopenia) in middle age and adulthood. With increasing muscle mass, anabolic (Manufacturer) hormones increase and catabolic (decomposer) hormones decrease. Testosterone is considered one of the anabolic hormones, which decreases in the serum after muscle loss, but instead of cortisol, which is a catabolic hormone, it shows the reverse of this process due to the increase in life. Resistance training shows a greater increase in increasing testosterone compared to old age. This research, which has been conducted as a review, has tried to investigate and evaluate the research in the last 10 years in resistance training with high and moderate intensity in the reduction and increase of testosterone and cortisol hormones. The results of this research show that moderate and high intensity resistance training in middle-aged and elderly people increases testosterone and decreases cortisol. But due to the fact that resistance training with high intensity leads to injury, this exercise is recommended for elderly people with moderate intensity at least once a week. However, high-intensity training two sessions a week is recommended for middle-aged people.